Modelo para a operacionalização da atividade de remanufatura - Medeiros, Flaviani Souto Bolzan (2020)
The depletion of natural resources and the impacts caused to the environment show that the current modes of production and consumption are distant from sustainability, which points to the need for changes in search of solutions in order to achieve a balance between development and sustainability and the preservation. In this sense, in a move towards more sustainable practices and more circular flows, remanufacturing has been gaining prominence as an important option for recovering end-of-life products instead of discarding them, thus helping to conserve resources and reduction of polluting emissions. Given the above, the objective of this thesis is to develop a model for the operationalization of the remanufacturing activity. To this end, Design Science Research was adopted, whose data collection techniques consisted of a systematic review of the literature (in order to list those items considered important for this sector) and semi-structured interview with those responsible for remanufacturing in the selected companies, in order to evaluate the built model. Among the results obtained, it should be noted that, on the one hand, not all items listed through the systematic literature review are present in the environment of the companies analyzed, such as: information and material flows, legislation and the relationship among stakeholders in remanufacturing. On the other hand, other elements have emerged, such as challenges, barriers and / or difficulties in working with remanufacturing. Therefore, based on the elaborated work, on a practical level, it is aimed to contribute so that the remanufacturing spreads to a larger number of companies in the most different sectors in the market. At a theoretical level, it is expected that the practice will become better known and be more widespread in society, so that companies, individuals and society itself can increasingly enjoy the environmental, economic and social benefits provided by the activity.